Legal Impact of Intimate Partner Violence Against Women (2018)
Introduction: Women victims of intimate partner violence, examined at the South Regional Office of the National Institute of Legal Medicine and Forensic Sciences (INMLyCF) in Colombia, expressed their opinion on the care procedure; some of them admitted abandonment of action, their interest to minimize domestic violence, or the foundations for the report. The legal intervention offers guidance on their rights and identifies expectations to restore them. Methods: This is a quantitative descriptive study in which sociodemographic aspects of both the victim and the alleged aggressor were analyzed. The data were collected by a semi-structured interview and the administration of the Campbell, O’Sullivan, Roehl and Webster’s Danger Assessment (da) Scale [1], cited in the protocol for assessing the risk of deadly violence against women prepared by the National Institute of Legal Medicine and Forensic Sciences [2]. 8Results: Some users ignore the steps of the care procedure for women victims of gender-based violence, but they manage to clear up their expectations during the report. The level of education of suspected perpetrators is inversely proportional to violence. Some triggers of conflict are mentioned, and psychoeducational therapies with cognitive-behavioral guidance are proposed to alleged aggressors, offering restorative measures to female victims. Conclusions: Although they did not know the care procedure, upon initiating it through the report, most of the women participating in the study described it as good. They supplied sociodemographic data that, combined with the results, allow to propose improvements in care, such as psychotherapies for alleged aggressors, based on the piloting that provided a new vision for the management of affected population.